Cardiorespiratory fitness as a mediator in the relationship between lung function and blood pressure in adults - Almeida,F.R. (2022)
It is unclear whether physical activity and cardiorespiratory fitness (CRF) are pathways that link low pulmonary function (LPF) to increased blood pressure (BP). Therefore, we investigated the extent to which CRF and moderate-to-vigorous physical activity (MVPA) mediate the relationship between LPF and high BP in adults. We conducted a cross-sectional study with 1,362 participants that underwent cardiopulmonary exercise testing (CPET), spirometry, and wore an accelerometer to determine physical activity patterns. We performed mediation analyses using structural equations considering peak oxygen uptake (V̇O2) and MVPA as mediators, forced vital capacity (FVC) and forced expiratory volume in the first second (FEV1) as independent variables, and systolic and diastolic blood pressure (SBP, DBP) as dependent variables. The probability of alpha error was set at 5%. We found a significant total effect of FVC on SBP and DBP considering V̇O2 as mediator (P<0.01). Indirect effects were also significant, with 42.6% of the total effect of FVC on SBP and 77% on DBP mediated by V̇O2 (P<0.01). We did not observe a direct effect of FVC on SBP and DBP. Considering FEV1 as an independent variable, the total effect on SBP was also significant, as were the indirect effects, mediated by V̇O2 at 14.8% for SBP and 7.6% for DBP (P<0.01). We did not find an indirect effect of FVC or FEV1 considering the MVPA as a mediator. CRF mediates the pathway that links LPF and elevated BP. Therefore, CRF is more sensitive to variations in FVC and FEV1 than MVPA.